Galectin-1 Ameliorates Influenza A H1N1pdm09 Virus-Induced Acute Lung Injury - Bao, Jiaqi; Wang, Xiaochen; Liu, Sijia; Zou, Qianda; Zheng, Shufa; Yu, Fei; Chen, Yu (Frontiers in Microbiology, 2020)
Influenza remains one of the major epidemic diseases worldwide. Acute lung injury mainly caused by excessive pro-inflammatory host immune responses leads to high mortality rates in severe influenza patients. Galectin-1, an animal lectin ubiquitously expressed in mammalian tissues, is reported to play important roles in viral diseases. Here, we established murine and A549 cell models to explore the potential roles of galectin-1 treatment in H1N1pdm09-induced acute lung injury. We found that galectin-1 protein level was elevated in A549 cell culture supernatants and mouse BALF after H1N1pdm09 challenge. In vivo experiments showed recombinant galectin-1 treatment reduced wet/dry weight ratio, inflammatory cell infiltration in mouse lungs and mediated the expression of cytokines and chemokines including IL-1β, IL-6, IL-10, IL-12(p40), IL-12(p70), G-CSF, MCP-1, MIP-1α and RANTES in serum and BALF of infected mice. Reduced apoptosis and viral titers in mouse lungs were also found after galectin-1 treatment. As expected, galectin-1 treated mice performed reduced body weight loss and enhanced survival rate against H1N1pdm09 challenge. In addition, in vitro experiments showed that viral titers decreased in a dose-dependent manner and cell apoptosis in A549 cells reduced after recombinant galectin-1 treatment. Taken together, our findings indicate a potentially positive effect of Gal-1 treatment on ameliorating the progress of H1N1pdm09-induced acute lung injury and recombinant galectin-1 might serve as a new agent in treating influenza.